2002
DOI: 10.1007/bf03344068
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of interleukin-6 (IL-6) and interleukin-6 receptor (IL-6R) in thyroid nodules is associated with co-expression of CD30 ligand/CD30 receptor

Abstract: Data on the expression of interleukin 6 (IL-6)/interleukin 6 receptor (IL-6R) in thyroid nodules is scarce. Based on our recent data of CD30 ligand (CD30L)/CD30 receptor (CD30) in these nodules and on the knowledge that this signal stimulates IL-6 production in non-thyroid neoplasms, we wanted to evaluate the immunocytochemical expression of these 2 ligand/receptor systems in a large archival series of paraffin-embedded specimens. These specimens included 6 normal thyroids and 130 thyroid nodules. Co-expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…As discussed above, P2X 7 receptors are responsible for the release of IL-6 in human thyroid cancer cell lines [16]. It was revealed that the local expression of IL-6 is related to the aggressiveness of PTCs [34]. IL-6 could also increase mRNA and protein levels of XIAP in ovarian cancer cells, promoting chemoresistance by activating multiple signaling pathways including the PI3K/Akt pathway [35].…”
Section: Discussionmentioning
confidence: 97%
“…As discussed above, P2X 7 receptors are responsible for the release of IL-6 in human thyroid cancer cell lines [16]. It was revealed that the local expression of IL-6 is related to the aggressiveness of PTCs [34]. IL-6 could also increase mRNA and protein levels of XIAP in ovarian cancer cells, promoting chemoresistance by activating multiple signaling pathways including the PI3K/Akt pathway [35].…”
Section: Discussionmentioning
confidence: 97%
“…The protective role of IL-6 in OIS, as discussed below, occurs naturally in pituitary adenomas as a dynamic and slow mechanism, which results in a benign tumor with stable growth arrest. Interestingly, in other endocrine tumors like thyroid nodules, IL-6 (and its receptor) expression (Ruggeri et al 2002) and also OIS with an associated inflammatory secretome (Vizioli et al 2014) has been reported, suggesting that a senescence process involving IL-6 might also take place in thyroid tumor progression.…”
Section: Autocrine Il-6 Mediates Pituitary Tumor Senescencementioning
confidence: 99%
“…For example, IL-6 expression is related to aggressiveness of both papillary and medullary thyroid cancer [16]. Despite the growing number of reports indicating the complex interactions between inflammatory and angiogenic factors in the development of thyroid cancer, studies have concentrated on a small number of markers [17, 18]. Vesely et al [19] examined serum levels of IGF-I, HGF, TGF β 1, bFGF, and VEGF in 28 patients with thyroid gland tumors (14 adenomas, 14 papillary carcinomas) and compared these concentrations with those in healthy people.…”
Section: Introductionmentioning
confidence: 99%